Fast and efficient DNA crosslinking and multiple orthogonal labelling by copper-free click chemistry. - Shelbourne, M; Brown, T; El-Sagheer, A; Brown, T (2012)
Two new dibenzocyclooctyne-thymidine monomers were incorporated into oligonucleotides and crosslinked to azide-labelled complementary strands across the DNA grooves. Equivalent reactions were successful using a (bicyclo[6.1.0]nonyne) alkyne. Oligonucleotides containing internal cyclooctyne and amino groups were simultaneously reacted with azides and NHS esters of different fluorescent dyes to produce functional genetic probes.